Zu Theorie und Praxis einer allgemeinen Fremdsprachenmethodik (AFM) — Grundlegende Positionen und empirische Erfahrungen - Apelt, Walter (Wydawcnictwo Naukowe UAM, 1990)
On the basis of comprehensive theoretical and practical experience and research the author describes: (1) The social and educational necessity of GFLD as a fundamental strategy in foreign language teacher training. He underlines the importance of the development of a theoretical and scientific basic professional competence in prospective FL teachers with regard to foreign language teaching and learning, and not only methodical ‘skills and techniques’ of the classroom teaching; (2) relevant positions of GFLD: its subject, general tasks and educational aims in teacher training, as well as special ‘fields’ to be covered and taught such as foreign language teaching (FLT) as a scientific discipline and its aims, basic referential sciences (pedagogy, psychology,, linguistics etc.), historical aspects of leading methods and methodical strategies in FLT, the principles of FLT; (3) practical problems and actual experience in the teaching of GFLD at a university level.